Survival and variability over time from out of hospital cardiac arrest across large geographically diverse communities participating in the Resuscitation Outcomes Consortium. (October 2018) - Zive, D.M.; Schmicker, R.; Daya, M.; Kudenchuk, P.; Nichol, G.; Rittenberger, J.C.; Aufderheide, T.; Vilke, G.M.; Christenson, J.; Buick, J.E.; Kaila, K.; May, S.; et al.
Abstract: Background: The Resuscitation Outcomes Consortium (ROC) epi demiological regis try (Epistry) provides opportunities to assess trends in out-of-hospital cardiac arrest treatment and outcomes. Methods: Patient, event, system, treatment, and outcome data from adult (≥18 years) out-of-hospital cardiac arrest (OHCA) from 10 geographically diverse North American ROC sites over four 12-month epochs, from July 1, 2011 to June 30, 2015, were assessed. Descriptive statistics were used to characterize the sample and logistic regression assessed the association of study epoch and key covariates on survival. Results: Overall, 85, 553 patients were assessed by Emergency Medical Services (EMS) and 45, 516 (53.2%, site range 30.4%–69.9%) had resuscitation attempted by EMS. Patient and event characteristics were consistent except for increases in bystander CPR (41.3%–44.9%) and bystander AED application (3.9%–5.2%). EMS CPR depth and compression fraction increased while pre-shock pause interval decreased. Targeted temperature management was performed in 51.1% of admitted patients and early coronary angiography in 30.2%. Survival to hospital discharge improved (from 10.9% to 11.3% across epochs) with epoch significantly associated with survival (p < 0.001) showing an increasing trend in survival over time. (p = 0.02). Marked site variation in survival persisted within and across epochs (overall site range: 4.2%–19.8%). Patients with an initially shockable rhythm (VT/VF) had an overall survival of 32.2% (site range: 11.9%–47.1%) while survival in bystander witnessed VT/VF was 35.8% (site range: 12.9%–53.1%). Conclusions: Survival from adult OHCA in multiple large geographically-separate sites improved over the study period. Marked site differences in survival persist and addressing this variation is essential to improve outcomes from OHCA across North America.